Effect of VKORC1 – 1639 G > A polymorphism, body weight, age, and serum albumin alterations on warfarin response in Japanese patients - Yoshizawa, Misa; Hayashi, Hideki; Tashiro, Yoshio; Sakawa, Sonoko; Moriwaki, Hideaki; Akimoto, Takehide; Doi, Osamu; Kimura, Midori; Kawarasaki, Yoshinori; Inoue, Kazuyuki; Itoh, Kunihiko (Thrombosis research, 2009)
To establish individualized warfarin therapy, we investigated the contribution of genetic variations of vitamin K epoxide reductase complex subunit 1 gene ( VKORC1) – 1639 G > A and Cytochrome P450 2C9 gene ( CYP2C9) and clinical factors on warfarin sensitivity in Japanese patients. Genetic analyses of VKORC1 – 1639 G > A and CYP2C9 ⁎2, ⁎3, and ⁎4 were performed in 259 Japanese patients and 341 healthy subjects. We selected 259 patients who have been prescribed warfarin with a 1.5–3.0 range of prothrombin time normalized as an international normalized ratio for at least 3 months and investigated factors that contribute to individual variability in warfarin dose. Furthermore, multivariate analysis was performed to investigate a warfarin dosing algorithm. There were great inter-individual differences in warfarin maintenance dose in 259 patients, ranging from a minimum dose of 0.75 mg/day to a maximal dose of 8.00 mg/day. VKORC1 – 1639 G > A polymorphism, body weight, age, and serum albumin were found to affect the inter-individual variability. The dosing algorithm of warfarin maintenance dose was investigated by multivariate linear regression. The regression equation was able to account for 33.2% (R 2 Adj = 0.332) of the overall variability in warfarin dose.